Verismo in the works of Gian Carlo Menotti: a comparison with late nineteenth-century Italian opera - Chacon, Victor (My University, 1991)
The Medium, The Consul, and The Saint of Bleecker Street by Menotti attest to a continuation of the verismo strain observed in certain late-nineteenth-century operas, especially Cavalleria Rusticana and Pagliacci. The study parallels veristic elements in Menotti with these corresponding works by examining their musical and dramatic relatedness. It considers the theatrical aesthetic of the day in Italy and the reaction of verismo to the style of Verdian opera. It posits that late-nineteenth-century musical trends shaped verismo and poses five reasons for the emergence of verismo in Italy. The decline of the Italian economy ca. 1871, its effect on regions of the country, and its link with the general inactivity of opera productions up through the late 1880's are considered.Verismo is defined and its link with French literary naturalism is established. It is shown that verismo became the Italian counterpart of the French literary movement, Giovanni Verga as its Italian exponent.In twentieth-century operatic acting, the principles of Stanislavski and Felsenstein form the basis of a realist movement in opera. Felsenstein's exploration of the operatic medium "used music to create drama." The study shows that Menotti's realist style itself had links with Felsenstein's principles.The Medium (1946) is analyzed, including the work's symbolism, its slice-of-life quality, its believability, and its Romantic aspects, particularly the grotesque. The analysis embraces the work's musical style, its vocal writing, leitmotifs, and the appearance of arias and aria-like structures.The paper addresses neo-verismo specifically and proposes reasons for its decline. Changes in the critical view of opera in the 1950's and the bases upon which critics and scholars formed their assessments of Menotti's style are considered. The writer finally identifies three factors (realism, sensationalism, and contemporaneity) and offers them as an endorsement of neo-verismo. The writer argues for a reappraisal of the artistic strength of Menotti's three operas based on these universal factors.
Thesis (D. Mus. Arts)--University of Washington, 1991
Keywords: Theses--Music